Relevansi Pemikiran Paulo Freire terhadap pendidikan Kritis di Era Digital Perspektif Filsafat Islam - Fatahillah, Fatahillah; Widianingsih, Heni; Riyadi, Hendar; Huda, Miftahul; Ulpah, Ghina (CV. Ulil Albab Corp, 2025)
Paulo Freire's thoughts, especially his criticism of the banking model and the notion of problematic education, remain relevant to examine the challenges of education in the digital age. Learning transformation that utilizes modern technology is often trapped in a one-way knowledge delivery pattern that marginalizes the critical participation of students. Therefore, this study aims to analyze the relevance of Freire's thinking to the development of digital-based critical education, focusing on dialogical principles, the formation of critical awareness (conscientização), and efforts to overcome digital inequalities. This research uses a descriptive qualitative approach with the library research method. Data was collected through a search of academic literature in the form of books, scientific journal articles, and credible scientific sources that discuss Paulo Freire's thoughts and their application in the context of digital education. The analysis was carried out thematically to identify the linkage between Freire's principles and critical education practices in the digital age. The analysis shows three key findings. First, the concept of Freire model banking has an analogy with passive digital learning practices, so that the transformation towards problematic education requires a reconstruction of pedagogical relationships based on collaboration and reflection. Second, Freire's dialogical principles proved relevant in building digital critical awareness, encouraging students to criticize algorithmic bias, misinformation, and power structures in cyberspace. Third, the implementation of digital critical education is faced with the gap in digital access and literacy, but also opens up liberative opportunities for the democratization of knowledge through cross-border collaboration. The results of the study confirm that the relevance of Freire's thinking in the digital era lies in its ability to inspire humanistic, participatory, and transformative educational models. Educators and policymakers need to integrate dialogical principles and critical awareness into digital learning designs, while addressing structural barriers such as inequality of access to technology. Thus, digital education can function not only as a means of knowledge transfer, but also as a space of liberation that enables students to become active subjects of social change.